Genetic Diversity of Avocado (Persea americana Mill) From Southern Ethiopia Using SSR Markers - Degu, Hewan; Tadesse, Almaz; Kalousova, Marie (Journal of Science and Development, 2024)
Avocado (Persea americana M.) is a vital cash crop in Ethiopia. Understanding its population structure and allelic polymorphism is crucial for genetic improvement. However, the genetic diversity of Ethiopian avocado remains underexplored. This study investigated the genetic diversity of avocado in Southern Ethiopia using Simple Sequence Repeat (SSR) markers. A total of 109 avocado trees from 16 districts were sampled, and 12 SSR markers were employed for analysis. The study detected 140 alleles across the 12 loci, averaging 11.7 alleles per locus. The average expected heterozygosity was 0.63 ± 0.12, while the observed heterozygosity was 0.48 ± 0.19, with all loci showing significant deviation from Hardy-Weinberg Equilibrium (HWE). The Analysis of Molecular Variance (AMOVA) indicated that approximately 5% of the genetic variation was among the 16 populations. Pairwise comparisons of population FST values revealed a lack of genetic differentiation in seven out of 48 paired comparisons. The Unweighted Pair Group Method with Arithmetic Mean (UPGMA), based on the Nei and Li similarity index, grouped the genotypes into three major clusters with bootstrap values of 100 and 5. Genetic distance analyses showed mixing of avocado trees from different districts. Discriminant Analysis of Principal Components (DAPC) categorized the samples into three groups, while model-based structure analysis subdivided them into two main genetic clusters. The moderate genetic diversity observed in the avocado germplasm is promising for the future of avocado cultivation in Ethiopia, suggesting the germplasm is a valuable source of alleles for genetic improvement. The mixing of avocado trees across districts indicates strong gene flow among populations. Furthermore, the significant variation among tree populations from different districts offers numerous opportunities for avocado breeding programs, providing hope for potential advancements in avocado cultivation.